Pre-amputation assessment using Roy's Adaptation Model - Dawson, S (British journal of nursing (Mark Allen Publishing), 1998)
This article describes the use of Roy's Adaptation Model as a framework for the assessment of a 69-year-old man undergoing a right below-knee amputation. The model recognizes that individuals are subject to internal and external stressors which can lead to adaptive or ineffective responses. The practitioner can help the patient to make adaptive responses to these stimuli through nursing interventions. The components of the model are illustrated using the patient as a case study. A comprehensive assessment in the four adaptive modes (physiological, self-concept, role function and interdependence) is undertaken and nursing diagnoses are made.